Land of the firebird : the beauty of old Russia - Massie, Suzanne (1980)
A beautifully written history of the now vanishing culture of pre revolutionary russia. A Culture which produced some of the most imspiring art, literature, dance and music the world has ever known.
To serve God and uplift humanity -- Radiant and many-colored Kiev -- "This happened for our sins" -- Holy Moscow: The Third Rome -- Inside and outside the walls of the Kremlin -- A rebel in his own land -- The first Romanovs -- The Great Peter -- Elizabeth: Bright colors and gilt -- Catherine: "A mind infinitely more masculine" -- The years of war and peace -- The old and true ways -- The treasure house -- Alexander Pushkin -- "Soul-inspired flight": The arts in Pushkin's time -- Death of the poet -- The Babylon of the snows -- The expansive countryside -- Heroes and anti-heroes -- The wanderers and the mighty handful -- Ice slides and Easter eggs: Russia celebrates -- Merchant Princes -- Petipa and the Imperial Ballet -- The world of art -- Diaghilev and the ballets russes -- The Avant-Garde.
Includes bibliographical references (pages 461-472) and index.
Keywords: Art, Russian; History